Impact of public debt on economic growth: a quantile regression approach - San, Chen Kong; Chin, Lee (SAGE Publications, 2023)
This study aimed at investigating the nexus between government debt and its determinants in the context of sustainable economic growth for 97 countries over the period from 2004 to 2018 by employing a panel data quantile regression and comparing it across a fixed-effects model and a generalized method of moments (GMM) model. The different touches of debt on economic growth were analysed. The quantile regression estimates revealed that government debt has various impacts on economic growth, relying on the degree of economic performance. Government debt negatively affects economic growth across all the quantiles. More interestingly, the quantile regression estimates indicated that in countries with a very low level of real GDP per capita growth, government debt has a stronger pernicious effect on economic growth compared to upper-middle and high-income countries. Hence, our results provided insightful information for policy makers in designing appropriate fiscal policies particularly for low- and lower- middle-income countries to mitigate the negative effect on economic growth, and it should be maintained at a low and reasonable level to promote sustainable economic growth. JEL Classification: E61, E62, E63, H63, O4, O40